Module Nusantara Programme 2024 Students Inbound Usu 'Siberu Dayang' Application of The Nusantara Concept, forever Meaningful from Holistic Activities (Diversity, Reflection, Inspiration) in North of Sumatra - Siregar, Ameilia Zuliyanti; M. Ikhsan Siregar; Mahathir Muhammad; Raihan Azhari Sagala (Charity : Jurnal Pengabdian Masyarakat, 2025)
The 2024 Independent Student Exchange Program (PMM) is an activity launched by the Ministry of Education, Culture, Research and Technology. One of the important components in PMM is the Nusantara Module, which is designed to provide students with direct experience of cultural diversity in various regions in Indonesia, especially in North Sumatra. PMM is a semester-long domestic student exchange program that invites students from various regions to study at the best universities outside their home region, with credit recognition of up to 20 credits. This program aims to improve students' hard skills and soft skills through various activities. The Nusantara Module in PMM 2024 includes four types of activities: diversity, inspiration, reflection and social contribution, which are guided by the Nusantara Module Supervisor. It is hoped that this activity can increase students' understanding of cultural diversity, strengthen their sense of nationality, encourage active participation in community service activities, and develop social and intercultural skills. The University of North Sumatra accepted 189 students from 82 universities in PMM 2024, with various teaching methods including lectures, FGDs, seminars, talk shows, and training conducted around Medan, as well as in several districts, such as Deli Serdang, Langkat, Simalungun, Karo, and Tobasa.